Auxin production by rhizobacteria was associated with improved yield of wheat (Triticum aestivum L.) under drought stress. Issue 4 (21st March 2018) - Raheem, Asif; Shaposhnikov, Alexander; Belimov, Andrey A.; Dodd, Ian C.; Ali, Basharat
ABSTRACT: Drought tolerant rhizobacteria of the genus Bacillus, Enterobacter, Moraxella and Pseudomonas colonizing the root system of Acacia arabica were isolated to mitigate the drought stress of wheat ( Triticum aestivum L.). In vitro auxin production by rhizobacteria was quantified by Ultra High Performance Liquid Chromatography (UPLC). Analysis of the crude extracts detected the indole-3-acetic acid (IAA), indole-3-carboxylic acid (ICA) and indole-3-lactic acid (ILA). Highest IAA production of 25.9 µg ml −1 was observed for Bacillus amyloliquefaciens S-134. Pot trials were conducted to evaluate the role of rhizobacteria to enhance the growth of wheat at different water regimes. At highest water stress i.e. 10% field capacity (FC), significant improvement of shoot length was observed with B. amyloliquefaciens S-134. For yield parameters, B. muralis D-5 and E. aerogenes S-10 recorded 34% and 1 fold increases for spike length and seed weight, over respective control at 10% FC. Mixed culture combinations of M-2 ( B. thuringiensis S-26, D-2, B. amyloliquefaciens S-134, B. simplex D-11) and M-3 ( M. pluranimalium S-29, B. simplex D-1, B. muralis D-5, P. stutzeri S-80) showed significant improvement for tillers and number of spikelets. In conclusion, application of the drought tolerant rhizobacteria can help to overcome productivity losses in drought prone areas.